Rediseño y readecuación, con enfoque social y turístico, de una antigua residencia patrimonial ubicada en la ciudad de Latacunga - Vargas Berrazueta, Marissa Salomé (2019)
This assignment proposes an integral project that consists in the redesign and readjudment of a heritage house located in Latacunga city, which requires an inmediate intervention to conserve the original architecture of the republican era. The purpose of this project consists to revive the characteristics of republican life, to generate a fusion between XIX century and todays architecture. It’s considered three main spaces: A coffee library, art galleries and a lodging area, whose common objective is to generate experience to national and international visitors. The interventions are made based on the concept of the fabric worked on the Jacquard loom and highlight in each space the original materials of the building, such as pumice stone and woodwork. Vegetation plays an important role that integrates interior and exterior spaces, which will be functional and aesthetically pleasing for young people and adults with an interest in culture. It handles a chromatic given especially by the colors of stone, wood and vegetation that provide warmth and harmony to the space, contrasted with primary colors to give a touch of joviality, and neutral colors such as black and white to evoke a sophisticated atmosphere. In this way an important architectural piece of the historical center will be conserved and additionally it will contribute to the culture and tourism of Latacunga city.